2014
DOI: 10.21608/ejaj.2014.63690
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some Chemical Substances as Inducers forTomato Resistance Against Root-Knot Nematode, Meloidogyne incognita

Abstract: The potency of the some chemicals from different groups known as inducers of systemic acquired resistance (SAR) viz., acetylsalicylic acid (ASA), DL-3aminobutyric acid (BABA), 2,6-dichloroisonicotinic acid (INA), 5-chlorosalicylic acid (CSA), nitrosalicylic acid (NSA),salicylic acid (SA),ascorbic acid (AS), and selenium (SE) in reducing reproduction Meloidogyne incognita in tomato plants cv. Castel rock was investigated under greenhouse conditions. Supplying chemicals three days-before nematode inoculation sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Ascorbic acid followed the SA and DKP in reduction of number of galls and egg masses and females in tomato root system. Similar results [16], mentioned that as almost inter in the synthesis of mitochondrial hydroxyproline proteins which regulate the cyanide-resistant respiration and this will be in a large amount in resistant plants [17]. Current work showed that application of DKP to the root system inducer side reduced the nematode parameters in the receptor root parts.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Ascorbic acid followed the SA and DKP in reduction of number of galls and egg masses and females in tomato root system. Similar results [16], mentioned that as almost inter in the synthesis of mitochondrial hydroxyproline proteins which regulate the cyanide-resistant respiration and this will be in a large amount in resistant plants [17]. Current work showed that application of DKP to the root system inducer side reduced the nematode parameters in the receptor root parts.…”
Section: Discussionsupporting
confidence: 61%
“…In a previous study spry of salicylic acid achieved the highest reduction percentage of final number of root galls, egg-masses and nematode population of Meloidogyne incognita infecting tomato plants under greenhouse conditions [32]. The pioneer effect of SA in providing a good growth of tomato plants may be revealed to the reduction in root-knot nematodes infestation and reproduction and inhibition of the penetration rate and/or the establishment of the feeding sites by the invading juveniles [16]. Induction of resistance in various crops by SA recorded; the mode of action may be depend on the induction of pathogenesis-related protein (PR protein) [33].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In another study, Molinari (2008) found 45 mM SA solution as soil drench or 0.5-1 mM root dip significantly reduced Meloidogyne reproduction (by 20 to 25%). Soil drench of SA and ASA reduced M. incognita reproduction on tomato roots (Anter et al, 2014). Also, Mostafanezhad et al (2014a), found that soil drench and spraying tomatoes with SA significantly reduced the diameter of M. javanica galls, numbers of galls and egg masses.…”
Section: Resultsmentioning
confidence: 94%
“…Natural nematicides, organic and inorganic amendments, biological control, and induced resistance have all been the subject of research (Oka et al, 2000). The purpose of resistance inducers or elicitors is to activate the plant's defense mechanisms through the use of certain chemicals or biotic agents (Baysal et al, 2003;Silva et al, 2004;Bonaldo et al, 2005, Dias-Arieira et al, 2012, and Anter et al, 2014. Systemic acquired resistance (SAR) and induced systemic resistance (ISR) are two known means of developing plant resistance to pests and diseases.…”
Section: Introductionmentioning
confidence: 99%